Synergistic Dose Permutation of Isolated Alkaloid and Sterol for Anticancer Effect on Young Swiss Albino Mice - Aljarba NH; Ali H; Alkahtani S (Dove Medical Press, 2021)
Nada H Aljarba,1,* Huma Ali,2,3,* Saad Alkahtani4 1Department of Biology, College of Science, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Chemistry, Maulana Azad National Institute of Technology, Bhopal, 462003, MP, India; 3Pinnacle Biomedical Research Institute, Bhopal, 462003, MP, India; 4Department of Zoology, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia*These authors contributed equally to this workCorrespondence: Huma AliDepartment of Chemistry, Maulana Azad National Institute of Technology, Bhopal, 462003, IndiaEmail humali.manit@yahoo.comIntroduction: Synergy is defined as an interaction of some substances that cooperate to give rise to the combined effect greater than the sum of their individual effects. It is a natural strategy that has evolved by nature to more efficacy with low cost.Methods: This study is designed to evaluate the chemopreventive effect of a combined drug sample which is prepared by mixing an equal portion of stigmasterol and palmatine isolated from Azadirachta indica and Tinospora cordifolia respectively at a concentration of 100 mg/kg and 200 mg/kg body weight during the whole concentration.Results: At the end of the study, it was found that this combined drug sample decreased the number of tumors and their size. This drug significantly reduced the serum level of glutamate pyruvate transaminase, alkaline phosphatase, glutamate oxalate transaminase, and bilirubin and enhanced the level of oxidative enzyme level of glutathione, superoxide dismutase, and catalase, and inhibit the level of lipid peroxides.Discussion: The result suggests that combined drug samples exhibit a chemopreventive effect which is better than the effect of individual drugs (stigmasterol and palmatine).Keywords: synergistic effect, anticancer, palmatine, stigmasterol, Swiss albino mice